Characterizing the chemical composition of Tang Sancai wares from five Tang dynasty kiln sites. Issue 4 (March 2020) - Chang, Dongxue; Ma, Renjie; Zhang, Liangren; Cui, Jianfeng; Liu, Fuliang
Abstract: This article aims, firstly, to characterize the chemical composition of the body samples from the Tang Sancai kiln sites of Huangye, Huangbao, Liquanfang, Xing, and Qionglai. While Huangye, Huangbao, and Liquanfang are located near the capital cities of Chang'an and Luoyang, the local kiln sites of Qionglai in Sichuan province and Xing in Hebei province are selected for comparative study. We find that the body samples from these sites maybe all made of local clay. Kaolin is used for producing the body samples from the kiln sites of Huangye, Huangbao, and Xing, but the content of K2 O and TiO2 are different among them. At the kiln sites of Liquanfang and Qionglai, however, iron-rich 'red clay' and calcium-rich 'yellow clay' are used instead. The article also aims to characterize the glaze samples from the two kiln sites of Huangye and Huangbao. We find that the Si/Al ratios of these samples are considerably higher than the respective body samples, which implies the intentional addition of siliceous raw material to the glaze. We suspect that only the yellow glaze samples from the Huangye Kiln are mainly made of kaolin, whereas the green glaze samples from both kilns and the brown glaze samples from the Huangbao Kiln are mainly made of other source of siliceous materials. The distinct chemical composition of the Tang Sancai wares from the kilns would be instrumental for tracing the provenance of Tang Sancai wares from other contexts.